A Comparative Study of the Image "Superfluous Person" in Chinese and Russian Literature - Yang, Yunjie (Journal of Theory and Practice of Social Science, 2023)
The image "superfluous person" is typical in world literature. It first appeared in Russia in the first half of the 19th century, then came into China with many translations of Russian literature, and was localized in China as time went by. The "superfluous person" images in Chinese and Russian literature have many differences due to the different social and historical conditions, but their spiritual core is basically the same. This paper makes a systematic and comparative study of the images of "superfluous person" in Chinese and Russian literature and finds that they are highly similar in their background, education and temperament. At the same time, based on this, the study also explores the significance of literary history, realistic significance and value enlightenment of the comparative analysis.